Antimalarial activity and interactions between quinine, dihydroquinine and 3-hydroxyquinine against Plasmodium falciparum in vitro. - Nontprasert, A; Pukrittayakamee, S; Kyle, D; Vanijanonta, S; White, N (1996)
The antimalarial activities of quinine, dihydroquinine (a natural impurity found in commercial pharmaceutical formulations of quinine) and 3-hydroxyquinine (the principal metabolite of quinine in humans) were tested both individually and in pairs against 5 strains of Plasmodium falciparum isolated from patients in Thailand. The median inhibitory concentrations (IC50) were similar for quinine (168 nmol/L, range 68-366), and dihydroquinine (129 nmol/L, range 54-324), and both were significantly lower than that of 3-hydroxyquinine (1160 nmol/L, range 378-3154) (P = 0.027). When these drugs were tested in combination, there was no evidence of synergy or antagonism, as determined by fractionary inhibitory indices and isobolograms. Quinine and its impurity, dihydroquinine, have equivalent antimalarial activities which are approximately 10 times greater than that of the metabolite 3-hydroxyquinine. These 2 compounds, which are not usually measured in specific drug assays, contribute to antimalarial activity after quinine administration.